DETERMINATION OF POLYSACCHARIDE CONTENTS IN CHINESE FRUIT BY GAS CHROMAROGRAPHY - T. Cui; X. Y. Li; Z. Gao (Journal of Animal and Plant Sciences, 2015)
This paper analyzes fifteen common fruits in northernChina,such as five varieties of apples, pears, peaches, and melons,as well as three varietiesof grapes, for non-digestible polysaccharides (NDPS) content. Through the use of the acid hydrolysis-GC method, the results show that the total polysaccharides (TPS)content of the fruits ranges from 0.08%(grape) to 1.30% (kiwi fruit). Furthermore,the content of water-soluble polysaccharides (SPS) in TPSrange from 17.7%(kiwi) to 86.3% (peach). The content of non-digestible polysaccharides (NDPS)in the various fruits is also significantly different.
Keywords: Fruit; non-digestible-polysaccharides; polysaccharide; gaschromatography